1999
DOI: 10.1074/jbc.274.20.14224
|View full text |Cite
|
Sign up to set email alerts
|

Ras Regulates the Association of Serum Response Factor and CCAAT/Enhancer-binding Protein β

Abstract: The serum response element (SRE) is a promoter element essential for transcriptional activation of immediate early genes, such as c-fos and early growth response-1, by mitogenic signals. Several transcription factors bind the SRE, including the serum response factor (SRF), the ternary complex factor, and the CCAAT/ enhancer-binding protein ␤ (C/EBP␤). The C/EBP␤ mRNA encodes three translation products of 38, 35, and 20 kDa. p35-C/EBP␤ activates transcription of the SRE in an SRF-dependent fashion, whereas p20-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 21 publications
2
57
0
Order By: Relevance
“…While there is no evidence that Ser-103 phosphorylation is required in that context, it may be possible that in a di erent promoter architecture, such as that found in the SRF gene promoter, that Ser-103 may be important. Another recent interesting report has shown that Ras regulates association of SRF with C/EBP-b to stimulate transcription (Hanlon and Sealy, 1999). Although, the role of Sp1 in this mechanism was not addressed in this report, it is interesting to speculate that Sp1 may promote an SRF ± C/EBP-b complex.…”
Section: Discussionmentioning
confidence: 77%
“…While there is no evidence that Ser-103 phosphorylation is required in that context, it may be possible that in a di erent promoter architecture, such as that found in the SRF gene promoter, that Ser-103 may be important. Another recent interesting report has shown that Ras regulates association of SRF with C/EBP-b to stimulate transcription (Hanlon and Sealy, 1999). Although, the role of Sp1 in this mechanism was not addressed in this report, it is interesting to speculate that Sp1 may promote an SRF ± C/EBP-b complex.…”
Section: Discussionmentioning
confidence: 77%
“…C/EBP␤ is a CCAAT enhancer-binding protein and is critical for normal proliferation and differentiation of mammary epithelial cells (29,30,34,38) as well as numerous other cell types (27,28). It has also been shown to transactivate the c-fos serum response element upon activation of the Ras-dependent signaling pathway in response to mitogenic stimulation (31). C/EBP␤ is found to be constitutively expressed in the liver, intestine, lung, adipose tissue, spleen, and kidney (39 -43) and plays an important role in adipocyte (40,44), hepatocyte (45), and mammary gland differentiation (29), as well as in ovulation (32,46).…”
Section: Discussionmentioning
confidence: 99%
“…Both stimulatory and inhibitory C/EBP␤ isoforms were expressed in macrophages, but repression occurred because the 16-kDa C/EBP␤ is a dominant negative factor that represses transcription when expressed at 20% the level of the stimulatory 37-kDa C/EBP␤ (24). Expression of the inhibitory C/EBP␤ represses promoters containing C/EBP sites such as the HIV-1 LTR (6) and also disrupts the function of the ubiquitously expressed serum response factor (55). Therefore, cells that express high levels of inhibitory C/EBP␤ may have global inhibition of multiple promoters.…”
Section: Discussionmentioning
confidence: 99%